Mechanism of cementite decomposition in 100Cr6 bearing steels during high pressure torsion. (December 2020) - Qin, Yu; Mayweg, David; Tung, Po-Yen; Pippan, Reinhard; Herbig, Michael
Abstract: Severe plastic deformation leads to cementite decomposition in pearlitic and martensitic alloys, resulting in high-strength nanocrystalline ferrite. This effect can be employed to strengthen pearlitic wires but it can also be associated with material failure by white etching cracks (WECs) that are primarily known to concern bearings or rails. We investigate the decomposition of spheroidal cementite in the martensitic bearing steel 100Cr6 with 62 Rockwell hardness during high pressure torsion at 9.5 GPa applied pressure. The hard martensitic matrix and the even harder spheroidal cementite precipitates behave plastically very differently. The enforced macroscopic plastic deformation is almost entirely carried by the matrix. Plastic material flow of the matrix around the spheroidal cementite leads to wear of the spheroidal cementite as indicated by continuously increasing levels of chromium in the matrix. Plastic deformation of spheroidal cementite via dislocation gliding supposedly accelerates this process as slip steps generated thereby are preferential sites of wear at the matrix/cementite interface. Larger spheroidal cementite precipitates are more prone to plastic deformation and to decomposition than smaller ones. The mechanism likely holds true in general for multiphase materials with large strain difference between phases subjected to high pressure torsion. Although the formation of WECs in 100Cr6 bearings might be slowed down by reducing the size of the spheroidal cementite precipitates, it is unlikely that this could entirely prevent this failure mechanism. Graphical abstract: Image, graphical abstract